Design of one axis three position solar tracking system for paraboloidal dish solar collector. (2016) - Parthipan, J.; Nagalingeswara Raju, B.; Senthilkumar, S.
Abstract: Solar Tracking System plays a vital role in the maximum generation of solar energy. However, the design of the sun tracker which was currently in use is very complicated and expensive. Those sun tracker units are heavy and seems to be difficult to install and prone to breakdown. This project aims to design an automatic Solar Tracking system which overcomes the above mentioned problems. In this process one axis three position solar tracking system was developed, to reduce the complexity and to shut down the cost and the same has been tested. Taking into consideration, the high efficiency with the lower cost, Light Dependent Resistor (LDR) sensors have been used in this project to track the sunlight position. Two LDR sensors one facing East and other facing West senses the intensity of sunlight and the result will be compared. The difference in the intensity will be calculated by the Programmable Interface Controller (PIC controller) which was fixed below the paraboloidal dish solar collector. If there is any difference in values, the controller sent the signal to the DC geared motor that passes through the amplifier which amplifies the signal according to that of DC geared motor. At once the motor receives the signal it tilts the solar collector. The above process will continue till the intensity of sunlight received by both the sensors is same. In this way, paraboloidal dish solar collector collects the maximum sunlight which will be converging to a black receiver for the maximum heat production. The test result shows that, the one axis three position tracking device is able to track and follow the Sunlight intensity in order to get maximum solar energy in the form of heat irrespective of the motor speed.